The Effect of a diabetes education component on the self-health care practices of diabetic women in a selected tertiary hospital - Abrugena, Vivienne Fallarme
This study sought to assess the effectiveness of the diabetes education component on the self-health care practices and self-efficacy; skills on blood glucose monitoring and insulin administration of women with diabetes at the Philippine General Hospital. The specific objectives were to determine any significant differences in the level of knowledge; blood glucose monitoring and insulin administration skills; self-reported measures of self-care practices and self-efficacy among female patients before being seen by a diabetes nurse educator and within a month after and to describe the different perceived roles of women with diabetes and how these roles are affected by the disease. The Before-After research design was utilized in the study and participants were chosen based on a given inclusion/exclusion criteria. Fifty-four diabetic women were included in the study and the group was provided the diabetes health education. A diabetes knowledge and self-health care practices and self-efficacy test were conducted and measured before and after the Diabetes Health Education Program. Skills on blood glucose monitoring and insulin administration were also measured before and after the diabetes health education utilizing a skills checklist. Results showed a signficant difference in the level of knowledge (p-value=<.01); skills on blood glucose monitoring (p-value=<.01) and insulin administration (p-value=<.01) of the study group before and fter the diabetes health education. Four health practices: monitor blood glucose at home (13.3% to 33.3%; frequency of self-examining the feet (80% to 100%; ease of maintaining an acceptable blog glucose level (mean of 3.5 to 2.51); and exercise>90 mins/week (8.9% to 13.3%) increased/improved before and after the diabetes health education. There was a decrease in the health practice of visit to a nutritionist/dietician of the study group (17.8% to 4.4%) before and after the health education program on diabetes. Seven measures of self-efficacy improved before and after the diabetes health education: following prescribed diet (66.7% to 95.6%); exercise regularly (44.4% to 86.7%); regular home blood glucose monitoring (2.2% to 6.7%); balancing the diet to control glucose (95.6% to 100%); ability to recognize and treat low blood glucose (93.3% to 100%); keeping blood gllucose control when sick (91.1% to 97.8%); and talking about concerns to one's physician (97.8% to 100%). The self-efficacy measure of expressing feelings about diabetes to family and friends remained unchanged at 100% before and after diabetes health education. Diabetic women's perceived roles were focused on being a wife, mother, grandmother and daughter. Their illness brings about different changes into these roles and in the multi-tasks handled by women at home and in the community. Diabetes imposed demands that affect the women's role performance by generally perceived by the women in the study to be manageable.